DNA Double Strand Break Repair Pathways in Response to Different Types of Ionizing Radiation - van de Kamp, Gerarda; Heemskerk, Tim; Kanaar, Roland; Essers, Jeroen (Frontiers in Genetics, 2021)
The superior dose distribution of particle radiation compared to photon radiation makes it a promising therapy for the treatment of tumors. However, the cellular responses to particle therapy and especially the DNA damage response (DDR) is not well characterized. Compared to photons, particles are thought to induce more closely spaced DNA lesions instead of isolated lesions. How this different spatial configuration of the DNA damage directs DNA repair pathway usage, is subject of current investigations. In this review, we describe recent insights into induction of DNA damage by particle radiation and how this shapes DNA end processing and subsequent DNA repair mechanisms. Additionally, we give an overview of promising DDR targets to improve particle therapy.